Real‐time calibration of space zoom cameras based on fixed stars - Qi Xia; Naiming Qi; Dong Ye; Yubo Guo; Tianye Wang (IET Computer Vision, 2017)
Compared with fixed focus cameras, zoom cameras can be used to provide more precise measurements in space tasks. However, the calibration of zoom cameras in this case is a difficulty, as it is not convenient to set up a calibration device on the spacecraft. To solve this problem, the authors present a real‐time zoom camera calibration algorithm based on fixed stars. With the star images captured by the zoom camera, they firstly use a star identification method to recognise the identity of stars. By means a series of coordinate transformation, they are able to build the one‐to‐one mapping between the pixel coordinates and epoch celestial coordinates of the stars. Finally, the internal and external parameters of the zoom camera are obtained based on the thick lens zoom camera model. Simulation and experiment results show that the internal parameters of zoom cameras are rarely affected by the noise of latitude, longitude and time. Furthermore, the calibration precision and robustness of focal length reaches a satisfactory level.